2005
DOI: 10.1111/j.1473-2165.2005.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Proposed mechanisms of action for retinoid derivatives in the treatment of skin aging

Abstract: Skin aging (intrinsic aging) and photoaging (extrinsic aging) involve a similar process that leads to the typical creased appearance of the skin, with the progressive loss of its physical and biologic properties. Photoaging is a premature skin aging caused by long-term exposure to the ultraviolet B radiations of the sun, and is more frequently associated to skin cancer than intrinsic aging. Retinoids are natural and synthetic vitamin A derivatives. They are lipophilic molecules and penetrate the epidermis easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…Although the use of tretinoin is well documented in acne and photoaging treatment, retinol is a cosmeceutical which is not as irritating nor as potent as tretinoin. However, retinol is reported to increase water content and collagen synthesis [ 6,7 ] , as well as inhibit melanogenesis and matrix metalloproteinases (MMPs) involved in collagen disruption, thus improving skin texture and reducing the visibility of skin lines and wrinkles. Retinol is a nonprescription cosmeceutical product, particularly used as an alternative approach for sensitive skin that does not tolerate tretinoin.…”
Section: Nonprescription Retinoids and Vitamin A Derivatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of tretinoin is well documented in acne and photoaging treatment, retinol is a cosmeceutical which is not as irritating nor as potent as tretinoin. However, retinol is reported to increase water content and collagen synthesis [ 6,7 ] , as well as inhibit melanogenesis and matrix metalloproteinases (MMPs) involved in collagen disruption, thus improving skin texture and reducing the visibility of skin lines and wrinkles. Retinol is a nonprescription cosmeceutical product, particularly used as an alternative approach for sensitive skin that does not tolerate tretinoin.…”
Section: Nonprescription Retinoids and Vitamin A Derivatesmentioning
confidence: 99%
“…The cosmeceutical bene fi ts from vitamin A and its derivates lie in their ability as retinoids to regulate epithelial cell growth and differentiation and, fi nally, to normalize keratinization. Retinoids have been shown to have receptor-speci fi c effects on the skin, resulting in decreased roughness, facial wrinkling and fi ne lines [ 6 ] allowed for the synthesis of novel pharmacologic classes of compounds that have broader structural diversity with greater variance of pharmacological properties than natural retinoids. Topical use of retinoids has shown to be effective in the treatment of acne, photodamage, and psoriasis.…”
Section: Nonprescription Retinoids and Vitamin A Derivatesmentioning
confidence: 99%
“…UVR causes several acute effects in the skin, including immediate pigment darkening, delayed tanning, sunburn, epidermal thickening, as well as several immune responses. Most importantly, UVA and UVB radiation have been observed to contribute to the disruption of extracellular matrix, which is a characteristic symptom of photoaging (Sorg et al, 2005;Talwar et al, 1995). It has long been thought that UVB causes most damage, but it is becoming increasingly evident that the biological effects of UVA is significantly more important; UVA also penetrates the skin more deeply than does UVB (Dekker et al, 2005).…”
Section: Uv Rays and Skin Cancersmentioning
confidence: 99%
“…It has long been thought that UVB causes most damage, but it is becoming increasingly evident that the biological effects of UVA is significantly more important; UVA also penetrates the skin more deeply than does UVB (Dekker et al, 2005). The mechanism of UV radiation associated dermal damage includes, decreased collagen I and III synthesis, increased collagen degradation by TGF-β and activator protein A, infiltration of inflammatory cells predominantly by neutrophils into the dermis releasing ROS (Saha, 2012;Sorg et al, 2005;Talwar et al, 1995). Biomolecules weakly absorb UVA, but it can generate ROS, which oxidize proteins, DNA, and lipids (Cooke et al, 2000;Hattori et al, 1996;Struthers et al, 1998).…”
Section: Uv Rays and Skin Cancersmentioning
confidence: 99%
“…Retinoids are therefore ideal for the treatment of photoaging. Numerous studies have confirmed the clinical efficacy of various retinoids [45][46][47][48][49][50] .…”
Section: Retinoidsmentioning
confidence: 99%